Management of labour and delivery in congenitally corrected transposition of great arteries. Issue 10 (14th July 2015) - Dhir, S.; Racine, J.; Gratton, R.; Bergin, L.; de Vrijer, B.
<x xml:space="preserve">Abstract</x> A descriptive case report of the labour and delivery management of a 28‐year‐old woman who presented with congenitally corrected transposition of great arteries, dextrocardia, systemic ventricular dysfunction and junctional tachycardia. Patients with congenitally corrected transposition have a thin‐walled morphological right ventricle as the systemic circulatory pump. The stress of increased cardiac output can lead to congestive heart failure, systemic atrioventricular valve regurgitation and arrhythmias. We used minimally invasive continuous cardiac output monitoring, fluid balance optimization and good maternal pain control to prevent decompensation and achieve vaginal delivery with a good maternal and neonatal outcome.